TINJAUAN KRIMINOLOGI TERHADAP KEJAHATAN JUDI ONLINE DI WILAYAH KABUPATEN LANDAK - NIM. A1011201082, RUSLI (Jurnal Fatwa Hukum, 2024)
AbstractOnline gambling is the practice of gambling carried out over the internet, allowing individuals to participate in various forms of gambling games using electronic devices such as computers, tablets or smartphones. The existence of gambling is not something new in the history of Indonesian society; The practice of gambling has existed since ancient times until now. Various factors, including economic and social aspects, have a role in the development of gambling. As time goes by, gambling develops with various mechanisms and forms. Gambling is generally seen as a crime. In this research, data was analyzed using qualitative analysis methods. Qualitative analysis is research that is descriptive in nature, tends to use analysis and makes the meaning process more visible. The qualitative data analysis method is a method of in-depth data processing using data from observations, interviews and literature. Based on the research results, several factors were found that influence online gambling players in Landak Regency, including the person's own behavior, the influence of social media, peers and the social environment. There are six obstacles for members of the Landak Police in dealing with online gambling crimes in the Landak Regency area, namely: First, easy access for the public to online gambling sites, Second, online gambling sites often use techniques to hide their identity and location, Third, technological developments in the world of gambling online, Fourth, limited resources, Lastly, aggressive marketing strategies from online gambling sites. There are three efforts by the Landak Resort Police in dealing with online gambling crimes in the Landak Regency area, namely: First, they organize outreach programs to the community, Second, they provide understanding to the public that online gambling is a legal violation that can be punished, Lastly, the Landak Resort Police increase internal capacity.  Keywords: Gembling, Online, Development    AbstrakJudi online adalah praktik perjudian yang dilakukan melalui internet, memungkinkan individu untuk berpartisipasi dalam berbagai bentuk permainan judi menggunakan perangkat elektronik seperti komputer, tablet, atau ponsel cerdas. Keberadaan perjudian bukanlah sesuatu yang baru dalam sejarah kehidupan masyarakat Indonesia; praktek perjudian telah ada sejak zaman dahulu hingga kini. Berbagai faktor, termasuk aspek ekonomi dan sosial, memiliki peran dalam perkembangan perjudian. Seiring berjalannya waktu, perjudian berkembang dengan beragam mekanisme dan bentuk. Berjudi secara umum dipandang sebagai sebuah kejahatan. Pada penelitian ini untuk menganalisis data dengan menggunakan metode analisis kualitatif. Analisis kualitatif adalah sebuah penelitian yang sifatnya deskripsi, cenderung menggunakan analisis dan lebih menampakkan proses maknanya. Metode analisis data kualitatif adalah metode pengolahan data secara mendalam dengan data dari hasil pengamatan, wawancara, dan literatur. Berdasarkam hasil penelitian ditemukan beberapa faktor yang memengaruhi pelaku judi online di Kabupaten Landak, termasuk perilaku orang itu sendiri, pengaruh media sosial, teman sebaya, dan lingkungan sosial. Hambatan bagi anggota Polres Landak dalam menangani kejahatan judi online di Wilayah Kabupaten Landak ada enam yaitu: Pertama, akses mudah bagi masyarakat terhadap situs judi online, Kedua, situs judi online sering menggunakan teknik penyembunyian identitas dan lokasi mereka, Ketiga, perkembangan teknologi dalam dunia judi online, Keempat, keterbatasan sumber daya, Terakhir, strategi pemasaran agresif dari situs judi online. Upaya kepolisian Resor Landak dalam melakukan penanggulangan terhadap kejahatan judi online di Wilayah Kabupaten Landak ada tiga yaitu: Pertama, mereka menyelenggarakan program penyuluhan kepada masyarakat, Kedua, mereka memberikan pemahaman kepada masyarakat bahwa judi online merupakan pelanggaran hukum yang dapat dipidana, Terakhir, Kepolisian Resor Landak meningkatkan kapasitas internal.  Kata Kunci : Perjudian, Online, Perkembangan